The influence of the field orientation on the representativeness of the positional dynamics in soccer small-sided games - Couto, B. P.; Praça, G. M.; Gabbett, T. J.; Luchesi, M. S.; Oliveira, M. P.; Sayers, M. G. (International Journal of Sports Science & Coaching, 2024)
The aim of this study was to compare the positional dynamics in soccer small-sided games (SSGs) with either greater length (SSGlength) or width (SSGwidth) with official games. Twenty four Brazilian U-20 national-level players participated in six SSGs training sessions with two different SSG configurations: SSGlength (4v4, 40 m length and 26 m width) and SSGwidth (4v4, 26 m length and 40 m width). Positional dynamics variables were monitored and compared to official games. Linear mixed regression model was fitted using the situations as fixed effect, and, when appropriate, player and/or group as random effects. When compared to SSGlength and SSGwidth, official games showed a greater Relative Team Length, LPWratio, Spacial Exploration Index (SEI), and Strech Index, with a large or very large effect size. The SSGlength elicited higher values of Relative Team Width, LPWratio, and SEI when compared to SSGwidth. No significant differences were found between SSGlength and SSGwidth for Relative Team Length (small effect size), and SI (small effect size). Both group and player as random effects showed low variances. We concluded that the tactical behaviours during the 4v4 SSG differed substantially from the competitive tactical behaviour during the official games. In addition, changing the orientation of the playing field did not make the positional dynamics of the SSGs more similar to the official games.